Theatre workshops help Egyptian women fish retailers lobby for their rights - WorldFish (WorldFish, 2014)
Women fish retailers in Egypt are often forced to pay unofficial fees for their roadside market stalls. Exposure to the elements affects the women’s health and causes their produce to spoil, limiting their income. An interactive theatre project has helped boost the confidence and ability of these women to lobby their local government for retail licenses to protect their safety and rights as workers.